Butyrate: A Double-Edged Sword for Health?. Issue 1 (9th February 2018) - Liu, Hu; Wang, Ji; He, Ting; Becker, Sage; Zhang, Guolong; Li, Defa; Ma, Xi
Abstract: Butyrate, a four-carbon short-chain fatty acid, is produced through microbial fermentation of dietary fibers in the lower intestinal tract. Endogenous butyrate production, delivery, and absorption by colonocytes have been well documented. Butyrate exerts its functions by acting as a histone deacetylase (HDAC) inhibitor or signaling through several G protein–coupled receptors (GPCRs). Recently, butyrate has received particular attention for its beneficial effects on intestinal homeostasis and energy metabolism. With anti-inflammatory properties, butyrate enhances intestinal barrier function and mucosal immunity. However, the role of butyrate in obesity remains controversial. Growing evidence has highlighted the impact of butyrate on the gut-brain axis. In this review, we summarize the present knowledge on the properties of butyrate, especially its potential effects and mechanisms involved in intestinal health and obesity.